Early language screening at 30 months of age in Swedish child health services—a qualitative study of nurses' perspectives - Larsson, AnnaKarin; Häll, Amanda; Granér, Emma; Carlsson, Emilia (Frontiers in Pediatrics, 2025)
AimTo understand how nurses within the child-health services perceive the early language screening administered at 30 months of age.MethodsA qualitative study was conducted involving individual interviews with 15 nurses working in the child-health services of two districts in western Sweden. The interview data were analysed through content analysis.ResultsThe qualitative analysis yielded two main categories: (1) Experience and flexibility facilitate use of the screening method and (2) External factors influence administration as well as the assessment and analysis of screening results. Regarding the first main category, the nurses considered that the screening method often worked well, but their confidence in using it was influenced by the length of their working experience. The second main category highlights external factors influencing the nurses' administration of screenings and their analysis and assessment of screening results, such as the child's abilities and overall development, language barriers, parental expectations and waiting times in healthcare. The two main categories can be broken down into seven sub-categories.ConclusionsOur findings indicate that nurses' experiences with interpreting screening results vary depending on their professional background and on the children's abilities, with particular challenges arising in the case of immigrant children.